2020
DOI: 10.1091/mbc.e19-07-0375
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative single-cell assay for retrograde membrane traffic enables rapid detection of defects in cellular organization

Abstract: Retrograde membrane trafficking from plasma membrane to the Golgi and endoplasmic reticulum affects intracellular protein dynamics underlying cell function. Here, we developed split-fluorescent toxin reporters that enable a quantitative, sensitive, and real-time single-cell flow cytometry assay for retrograde membrane transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Kinetic time course experiments on retrograde trafficking across diverse conditions and cell lines can be reliably quantified by flow cytometry. Notably, we obtained high levels of reproducibility in K562 cells with calculated Z-factors of 0.92 and 0.96 for TGN and ER transport, respectively (Luong et al, 2020). A Z-factor > 0.5 is considered ideal for high-throughput screening (Zhang et al, 1999).…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Kinetic time course experiments on retrograde trafficking across diverse conditions and cell lines can be reliably quantified by flow cytometry. Notably, we obtained high levels of reproducibility in K562 cells with calculated Z-factors of 0.92 and 0.96 for TGN and ER transport, respectively (Luong et al, 2020). A Z-factor > 0.5 is considered ideal for high-throughput screening (Zhang et al, 1999).…”
mentioning
confidence: 79%
“…The assay depends on CTB's ability to bind GM1 at the cell membrane and the C-terminal KDEL-motif of the CTA2-chain's ability to bind the ER-retention KDEL-receptor (Lencer and Tsai, 2003). Additionally, we applied the split fluorescent protein (spilt-FP) technologies to CTx for single-cell flow cytometry (Feng et al, 2017;Luong et al, 2020). The CTA2 chain was engineered to include the split monomeric neon green2 (mNG211) peptide and was coexpressed in E. coli with the homopentameric CTB.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For these studies, the different GM1 species were applied to a HeLa cell line that endogenously lacks GM1. CTxB trafficking into the ER was quantitatively measured using a FACS-based split-GFP assay recently developed by our group (60). We found that only the short chain (≤ C14:0) or unsaturated GM1 species (≤ C22:1 Δ13 ), both lacking the C14*-motif, efficiently trafficked CTxB into the ER (Fig.…”
Section: Sorting Into Retrograde and Recycling Pathways By Bulk Membrane Flowmentioning
confidence: 95%